2018
DOI: 10.3390/nu10070834
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Role of Green Tea Polyphenols in Improving Fertility: A Review

Abstract: Sperm cells are highly sensitive to reactive oxygen species (ROS), which are produced during cellular oxidation. In normal cell biology, ROS levels increase with a decreasing antioxidant response, resulting in oxidative stress which threatens sperm biology. Oxidative stress has numerous effects, including increased apoptosis, reduced motion parameters, and reduced sperm integrity. In this regard, green tea polyphenols (GrTPs) have been reported to possess properties that may increase the quality of male and fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 114 publications
1
35
0
Order By: Relevance
“…For centuries, tea drinking is a popular Chinese culture. Regular tea consumption has several health benefits and improves fertility in humans and animals (Ding et al, ; Rahman et al, ). We noted an increase in sperm concentration in tea‐consuming population.…”
Section: Discussionmentioning
confidence: 99%
“…For centuries, tea drinking is a popular Chinese culture. Regular tea consumption has several health benefits and improves fertility in humans and animals (Ding et al, ; Rahman et al, ). We noted an increase in sperm concentration in tea‐consuming population.…”
Section: Discussionmentioning
confidence: 99%
“…l-theanine has been studied as a food additive and functional food in relation to human nutrition, and it has health-promoting, pharmacological and biological properties such as anti-cerebral ischaemiareperfusion injury, stress-reducing, antitumour, anti-ageing and anti-anxiety activities (Culetu, Fernandez-Gomez, Ullate, Maria, & Wilfried, 2016;. Green tea polyphenols (GTPs) increase the quality of male and female gametes mainly due to catechins which reduce the level of reactive oxygen species (ROS) both in humans and animals thereby improving fertility (Rahman et al, 2018). This article describes the useful applications and practical utility of green tea and l-theanine as feed supplement to improve production performances and provide potential health applications in livestock animals including poultry, fish and others.…”
Section: Introductionmentioning
confidence: 99%
“…Polyphenols have also been shown to influence fertility and sexual development; fetal health and the bioavailability of nutrients (LY, et al 2015). Some classes of polyphenols such as green tea catechins have been shown to have antioxidant properties, which improved fertility parameters, such as sperm concentration, motility, morphology, DNA damage, fertility rate, and gamete quality (RAHMAN et al, 2018). Also, cyanidin-3-O-glucoside at low doses improved the number and motility of the sperms, alleviating the seminiferous tubule injury caused by 3-chloro-1,2-propanediol (3-MCPD) (JIANG et al, 2018).…”
Section: Orange Juice and Its Bioactive Compoundsmentioning
confidence: 99%
“…Also, what mechanisms explain why orange juice presented protective metabolic effects in female offspring, but did not prevent breast cancer. Furthermore, the potential benefits of paternal consumption of polyphenols should be further investigated, as it has been shown that some classes of these bioactive compounds have positive effects on male reproductive parameters (JIANG et al, 2018;RAHMAN et al, 2018). Understanding orange juice and polyphenols consumption by fathers in their specific metabolic context (i.e.…”
Section: Mammary Gland Development and Susceptibility To Carcinogenesmentioning
confidence: 99%
See 1 more Smart Citation